Analysis Of Factors Affecting The Acceptance Of Hospital Information System Using Utaut Method In Budi Kemuliaan Hospital Batam Year 2021 - Lenny Simatupang; Irma Solvia; Karmila Kaban; Sri Lestari Ramadhani Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
The acceptance of the hospital information system using the UTAUT method at the Budi Kemuliaan Hospital Batam in 2021 is still a complaint and the computer-based SIMRS is not running optimally. The acceptance of the hospital information system using the UTAUT method is related to individual characteristics, performance expectations, business expectations, social and facilities. This study aims to determine the effect of receiving hospital information systems with the UTAUT method at Budi Kemuliaan Hospital Batam. This type of quantitative research with correlational techniques. The population in this study were users of the SIMRS application at Budi Kemuliaan Hospital Batam and a sample of 120 people. The collection of data with primary and secondary data and the data were analyzed by Multiple Regression test. The results showed a positive and significant influence between Hospital Information System Acceptance (individual characteristics, performance expectations/performance expectations, business expectations/business expectations, social influences/social influences, and facilitating conditions/facilitating conditions) on usage behavior/behavior. implementing SIMRS with the UTAUT method at Budi Kemuliaan Hospital Batam and it is recommended that the implementation of SIMRS then need to pay attention to the ease of users in using SIMRS and developers from SIMRS and the hospital need to work together in developing to create a SIMRS with business processes and needs the one in the hospital.